Using neutral cline decay to estimate contemporary dispersal: a generic tool and its application to a major crop pathogen. (20th March 2013) - Rieux, A.; Lenormand, T.; Carlier, J.; de, L.; Ravigné, V.; Nathan, Ran
Abstract Dispersal is a key parameter of adaptation, invasion and persistence. Yet standard population genetics inference methods hardly distinguish it from drift and many species cannot be studied by direct mark‐recapture methods. Here, we introduce a method using rates of change in cline shapes for neutral markers to estimate contemporary dispersal. We apply it to the devastating banana pest Mycosphaerella fijiensis, a wind‐dispersed fungus for which a secondary contact zone had previously been detected using landscape genetics tools. By tracking the spatio‐temporal frequency change of 15 microsatellite markers, we find that σ, the standard deviation of parent–offspring dispersal distances, is 1.2 km/generation1/2. The analysis is further shown robust to a large range of dispersal kernels. We conclude that combining landscape genetics approaches to detect breaks in allelic frequencies with analyses of changes in neutral genetic clines offers a powerful way to obtain ecologically relevant estimates of dispersal in many species.